Self-Regulated Learning Mediates the Impact of Word-Problem-Solving Teaching Instruction in Intrinsically Motivated Students: A Moderated Mediation Analysis - ., Ardianik; Masitoh , Siti; Arianto , Fajar (Journal of Ecohumanism, 2024)
Mathematical word problem-solving ability is important for academic success and future career opportunities. While teaching approaches focusing on word problem-solving have shown promise, the mechanisms driving their effectiveness, particularly the roles of self-regulated learning (SRL) and motivation, remain unclear. This study investigates the moderated mediation effects of motivation on word problem-solving abilities through SRL. A quasi-experimental study was conducted with 123 eighth-grade Indonesian students, divided into four classes. Two classes received word problem-solving instruction, while the others followed standard problem-solving instruction. Students' problem-solving abilities, SRL, and motivation were assessed before and after the intervention. Using the PROCESS Macro, we evaluated simple and moderated mediation effects. The findings revealed that the word problem-solving intervention significantly enhanced SRL, which in turn improved problem-solving abilities, particularly among intrinsically motivated students. This effect was not observed in extrinsically motivated students. This study provides a novel exploration of SRL as a mediator and motivation as a moderator in educational interventions, offering a comprehensive understanding of the mechanisms underlying successful problem-solving. It provides valuable insights for educational practitioners, emphasizing the importance of SRL and intrinsic motivation in promoting effective and equitable problem-solving skills.